An Islamic Boarding School English Language Ecology Framework for Sustainable Communication: A Case Study at Pesantren Darul Falah - Ulfatussyarifah Ulfatussyarifah (International Journal Corner of Educational Research, 2026)
Sustaining fluent English communication within Islamic boarding schools (pesantren) often presents a tension between intensive foreign language acquisition and religious-cultural preservation. Adopting the Modern Islamic Boarding School curriculum (Modern Kulliyyatul Mu'allimin Al-Islamiyyah/MMI inspired by KMI Gontor and refined by institutions such as Daar El-Qolam), this qualitative case study investigated the linguistic ecosystem at Darul Falah Islamic Boarding School to construct the Islamic Boarding School English Language Ecology Framework (IBS-ELEF) for sustainable communication. Data were collected over six months through in-depth interviews with 12 key informants (language directors, teachers, and student language officers), participant observation across daily campus language zones, and institutional document analysis. The findings revealed that sustainable English usage is driven by three interconnected ecological pillars: (1) a Structural-Institutional Pillar utilizing bi-weekly language rotations, morning vocabulary injections (mufrodat), and peer-led enforcement (Pengurus Bahasa); (2) a Socio-Religious Pillar re-contextualizing English as a medium for global Islamic advocacy (Da'wah-English); and (3) an Affective-Environmental Pillar fostering a low-anxiety, collective learning culture. These dimensions coalesce into the IBS-ELEF model, demonstrating that language sustainability relies on harmonizing institutional discipline, religious identity, and peer support rather than enforcing Western cultural assimilation. Practically, IBS-ELEF offers a contextually grounded, scalable blueprint for non-Western, religious-based ESL/EFL institutions striving to cultivate globally communicative learners while safeguarding their core values.